Selected readings in economic theory from Econometrica - Arrow, Kenneth J. (Cambridge, Mass. : M.I.T. Press, 1971)
Econometrica has been a major locus of contributions to price theory and other branches of economic theory.
Includes 2 articles in French.
Includes bibliographical references and index.
rpm 07/07/2017
Loans
Keywords: Economics; Econometrics